Analytical methods for biomass characterization and conversion - Dayton, David C. (Elsevier, 2020)
Analytical Methods for Biomass Characterization and Conversion is a thorough resource for researchers, students and professors who investigate the use of biomass for fuels, chemicals and products. Advanced analytical chemistry methods and techniques can now provide detailed compositional and chemical measurements of biomass, biomass conversion process streams, intermediates and products. This volume from the Emerging Issues in Analytical Chemistry series brings together the current knowledge on each of these methods, including spectroscopic methods (Fourier Transform Infrared Spectroscopy, Near-infrared Spectroscopy, Solid State Nuclear Magnetic Resonance), pyrolysis (Gas Chromatography/Mass Spectrometry), Liquid Chromatography/High Performance Liquid Chromatography, Liquid Chromatography/Mass Spectrometry, and so on. Authors David C. Dayton and Thomas D. Foust show how these can be used for measuring biomass composition and for determining the composition of intermediates with regard to subsequent processing for biofuels, bio-chemicals and bio-based products. Covers the broad range of techniques and applications that have been developed and perfected in the last decade Highlights specific analyses required for understanding biomass conversion to select intermediates Provides references to seminal books, review articles and technical articles that go into greater depth, serving as a basis for further study.--